HUBUNGAN MINAT MEMBACA BUKU ILMU UKUR TANAH DENGAN PRESTASI BELAJAR ILMU UKUR TANAH SISWA SMK NEGERI 1 PADANG - 8-16 . Alvina (CIVED, 2013)
The background of this research is the lack of interest in reading books Science of Geometery Land Competency Skills class X Architecture at SMK Negeri 1 Padang. The study aims to determine the relationship between interest in reading books Science  of Geometery Land learning achievement Science  of Geometery Land Competency Skills class X Architecture SMK Negeri 1 Padang. This research is a descriptive study is correlational. The research hypothesis is, "there is a correlation between interest in reading books Science  of Geometery Land to Geometery Land learning achievement of students of SMK Negeri 1 Padang". This study population is students of class X Skills Competency Architecture totaling 64 people and research is the study population. The research data were analyzed using SPSS version 17. From the results obtained by the analysis of Pearson correlation value of 0.354 and significance of the correlation value of 0.004 is less than 0.05. Means there is a significant correlation between interest in reading books Science of Geometery Land to Geometery Land learning achievement of students of SMK Negeri 1 Padang. Key words : minat membaca buku, prestasi belajar